Образовательные возможности игры в педагогическом процессе вуза - Альмурзаева, Б.К.; Кусанова, Б.Х. (My University, 2016)
Methods of investigation: theoretical analysis of the philosophical, psychological, pedagogical and methodological literature on the issue. As a result of the research presented the position of the Russian scientist MM Kashapova, to investigate the problem of formation of creative thinking professionals.
Keywords: educational Environment; training dialog; a game; active learning methods